Patrimonio alimentario y gastronómico del cantón La Maná provincia de Cotopaxi. - Guamán Chicaiza, Cristian Paúl (2021)
The present investigation was carried out in La Maná canton, Cotopaxi province, which had as objective the study of the Food and Gastronomic Heritage of the canton. The research has a qualitative methodological approach since data is collected in order to achieve an interpretation of results based on cultural aspects of the study area. In the first objective, the inductive method was applied in such a way that the method allowed to carry out a first analysis and compilation of primary and secondary information through the bibliographic review of books, journals, scientific articles, virtual documents and the PDOT of La Maná canton, in which the current state of the study area was identified, in this way it was possible to identify that the canton is made up of 5 parishes, so that 3 parishes are urban such as: El Carmen, El Triunfo and La Maná, in the same way 2 parishes are rural as: Guasaganda and Pucayacu. The main economic source of La Maná canton is agriculture and livestock. In the second objective, the ethnographic method was applied, since by means of the method it allowed to carry out an approach towards the key actors to collect relevant data through interviews, in the same way the files of the NICH (National Institute of Cultural Heritage) facilitating the inventory of the Intangible Cultural Heritage, area 4, gastronomy sub scope, to publicize the number of traditional dishes and their relevance to the food heritage of the canton, resulting in 12 gastronomic processes. In the same way, the agricultural products that are grown within the territory were identified, in which 14 products were identified that are the basis of the ingredients for the preparation of food in the territory, however, more relevance was given to 5 products that They are listed as patrimonial according to the Ministry of Culture and Heritage. In the third objective, the synthetic method was applied since by means of the method the organization and analysis of the most relevant data collected in the inventory was carried out, applying the computer technique that allowed the systematization of information. Carrying out the design and elaboration of a descriptive guide of the Food and Gastronomic Heritage directed to the inhabitants and tourists. Thus, it will serve as a dissemination tool to revalue the food heritage and gastronomy in the territory and strengthen the cultural identity in La Maná canton.